2017
DOI: 10.1149/2.1601712jes
|View full text |Cite
|
Sign up to set email alerts
|

Electrocatalysis of the Oxygen Reduction Reaction and the Formic Acid Oxidation Reaction on BN/Pd Composites Prepared Sonochemically

Abstract: Highly active and inexpensive electrocatalysts are critical for metal-O 2 batteries or fuel cells. In the present study, we synthesized single boron nitride nanosheet-supported palladium (BN/Pd) composites via a simple sonochemical method. The properties of the synthesized products were studied by X-ray powder diffraction (XRD), scanning electron microscopy (SEM), SEM energy-dispersive X-ray spectroscopy (SEM-EDX), transmission electron microscopy (TEM) and high-resolution TEM (HRTEM). The as-prepared BN/Pd co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 46 publications
1
11
0
Order By: Relevance
“…Our calculations agree well with a recently published experiment on BN@Pd composites which revealed an ORR activity comparable to that of the commercial Pt/C catalyst. 22 The calculated CO adsorption energies are À0.62 eV and À0.01 eV for h-BN@Cu and h-BN@Pd with B-vac., respectively. These energies are signicantly weaker than the CO adsorption energy on Pt (111), À1.65 eV, indicating less CO poisoning on h-BN@M compared to Pt (111).…”
Section: Resultsmentioning
confidence: 91%
See 2 more Smart Citations
“…Our calculations agree well with a recently published experiment on BN@Pd composites which revealed an ORR activity comparable to that of the commercial Pt/C catalyst. 22 The calculated CO adsorption energies are À0.62 eV and À0.01 eV for h-BN@Cu and h-BN@Pd with B-vac., respectively. These energies are signicantly weaker than the CO adsorption energy on Pt (111), À1.65 eV, indicating less CO poisoning on h-BN@M compared to Pt (111).…”
Section: Resultsmentioning
confidence: 91%
“…28 Zuo et al observed that Pd supported boron nitride retained its ORR activity aer 4000 cycles, while the halfwave potential of commercial Pt/C decreased by 33 mV. 22 These experiments indicate that depositing h-BN on metal supports is a promising technique to enhance the stability of noble metal supports while maintaining the activity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Experiments have shown that the ORR catalytic performance of h-BN-Pd materials in the presence of boron vacancies can attain catalytic activities similar to that of commercial Pt/C. [64] Thus, vacancies in ultrathin h-BN materials can enhance the catalytic activity of the substrate.…”
Section: Oxygen Reactionsmentioning
confidence: 99%
“…However, as the design of catalytic nanomaterials with enhanced thermal stability is desired, it is important to focus on emerging catalyst supports such as boron nitride-based materials, which besides possessing extremely high thermal, mechanical, and chemical resistance [ 16 , 17 , 18 , 19 ], have also been recently investigated as hydrogen storage platforms and in nanocatalysis [ 20 , 21 ]. When compared to other support materials such as oxides and carbon, the potential of boron nitride (BN) as an innovative support for selective reactions has been demonstrated, especially for processes requiring high temperatures [ 22 , 23 , 24 , 25 , 26 ], and it has been shown that Pd NPs supported on BN open prospects for many catalytic reactions, such as the hydrogenation of lactose, for example [ 23 , 27 , 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%